A Critical Appraisal of Probiotics for Mastitis Control - Rainard, Pascal; Foucras, Gilles (Frontiers in Veterinary Science, 2018)
The urge to reduce antimicrobials use in dairy farming has prompted a search for alternative solutions. As infections of the mammary gland is a major reason for antibiotic administration to dairy ruminants, mammary probiotics have recently been presented as a possible alternative for the treatment of mastitis. To assess the validity of this proposal, we performed a general appraisal of the knowledge related to probiotics for mammary health by examining their potential modes of action and assessing the compatibility of these mechanisms with the immunobiology of mammary gland infections. Then we analyzed the literature published on the subject, taking into account the preliminary in vitro experiments and the in vivo trials. Preliminary experiments aimed essentially at exploring in vitro the capacity of putative probiotics, mainly lactic acid bacteria (LABs), to interfere with mastitis-associated bacteria or to interact with mammary epithelial cells. A few studies used LABs selected on the basis of bacteriocin production or the capacity to adhere to epithelial cells to perform in vivo experiments. Intramammary infusion of LABs showed that LABs are pro-inflammatory for the mammary gland, inducing an intense influx of neutrophils into milk during lactation and at drying-off. Yet, their capacity to cure mastitis remains to be established. A few preliminary studies tackle the possibility of using probiotics to interfere with the teat apex microbiota or to prevent the colonization of the teat canal by pathogenic bacteria. From the analysis of the published literature, it appears that currently there is no sound scientific foundation for the use of probiotics to prevent or treat mastitis. We conclude that the prospects for oral probiotics are not promising for ruminants, those for intramammary probiotics should be considered with caution, but that teat apex probiotics deserve further research.